Burkholder & Johnson, Colonial Latin America - Seidel, Robert (Teaching History: A Journal of Methods, 1991)
It is fitting to look at Colonial Latin America in terms of efforts to invigorate the teaching of history in behalf of education, citizenship, and civilized discourse in a conflict-ridden and diverse world. In this milieu, the colonial history of Latin America can be exceedingly serviceable. The subject's difficulty is not the real problem; the entire historical enterprise is daunting. full of surprises and mystery, and hard to fit into the mold of easy generalizations. The problem lies rather in the historical profession's responsibility to bring subject matter to life and demonstrate this liveliness to students who may then become energized by it.